2023
DOI: 10.1088/1475-7516/2023/10/025
|View full text |Cite
|
Sign up to set email alerts
|

GW_CLASS: Cosmological Gravitational Wave Background in the cosmic linear anisotropy solving system

Florian Schulze,
Lorenzo Valbusa Dall'Armi,
Julien Lesgourgues
et al.

Abstract: The anisotropies of the Cosmological Gravitational Wave Background (CGWB) retain information about the primordial mechanisms that source the gravitational waves and about the geometry and the particle content of the universe at early times. In this work, we discuss in detail the computation of the angular power spectra of CGWB anisotropies and of their cross correlation with Cosmic Microwave Background (CMB) anisotropies, assuming different processes for the generation of these primordial signals. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…Since the GW and the CMB photon share the same geodesics under the same metric perturbation during their propagation, we expect that CGWB anisotropies have a noticeable correlation with these two CMB tracers. The cross-correlation between CGWB and CMB has been previously studied in [47,75,76], we here give the result based on NANOGrav data and show that it significantly affects the low ℓ of CGWB×CMB angular power spectrum. The a ℓm s of CMB temperature fluctuations are…”
Section: Cross-correlations Of Cgwb With Cmb and Gravitational Lensingmentioning
confidence: 59%
See 2 more Smart Citations
“…Since the GW and the CMB photon share the same geodesics under the same metric perturbation during their propagation, we expect that CGWB anisotropies have a noticeable correlation with these two CMB tracers. The cross-correlation between CGWB and CMB has been previously studied in [47,75,76], we here give the result based on NANOGrav data and show that it significantly affects the low ℓ of CGWB×CMB angular power spectrum. The a ℓm s of CMB temperature fluctuations are…”
Section: Cross-correlations Of Cgwb With Cmb and Gravitational Lensingmentioning
confidence: 59%
“…(2.30)(2.31), η in influences the transfer functions through the metric perturbations and projection effects from Spherical Bessel functions, potentially introducing model dependence to the anisotropies in the CGWB. However, in practice, we have observed that the varying specific value of η in does not appreciably alter any anisotropic signals noticeably provided that η in remains small (see also [47]). We therefore adopt η in = 10 −4 Mpc in the rest part of this paper.…”
Section: Jcap02(2024)016mentioning
confidence: 73%
See 1 more Smart Citation
“…An even clearer signature would be a broken powerlaw, but to test for such a feature will require even higher signal-to-noise ratios and hence take correspondingly longer time to probe observationally. A valuable source of information to further disambiguate between SMBHBs and GWBs of primordial origin may lie in the anisotropies of the GWB [121][122][123], in particular via the polarization of the GWB [124][125][126][127][128][129][130] and possibly the detection of singular GW sources as already searched for [131,132].…”
Section: Comparison With Other Gw Sourcesmentioning
confidence: 99%
“…[100], other related works can be found in refs. [94,[101][102][103][104][105][106][107].One of the leading aims of our present work is to establish the first complete analysis.…”
Section: Introductionmentioning
confidence: 99%